An examination of the drafting-responding process used to develop students' writing in an English Language for Academic Purposes Course - Quinn, Lynn (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2000)
Many students when they arrive at university do not possess the "cultural capital" (Bourdieu 1977) which is favoured by the institution. The purpose of the English Language for Academic Purposes (ELAP) course and the drafting-responding process is to help students to begin to acquire the "cultural capital" required to succeed at university. The research reported on in this thesis examined the drafting-responding process as it is used to develop students' writing in the ELAP course at Rhodes University. The process involved students submitting drafts of their essays on which they received constructive and formative feedback from their ELAP tutor. This feedback was then used to revise their essays before a final version was submitted for assessment. The research took the form of a case study with an essentially interpretive orientation. I examined the drafts (with the tutor's comments) and final versions of seven students' ELAP essays. Additional data was obtained by interviewing the students and the tutor. Underpinning my beliefs regarding the role of writing in learning as well as my orientation to research is an understanding of knowledge and learning as being socially constructed. All writing is embedded in and dependent on, not only the immediate social circumstances, but also the broader social and cultural context. In analysing and discussing the data in this research I used Halliday's (1985) definition of context, in which he draws a broad distinction between the immediate context of situation and the broader context of culture The research findings showed that the drafting-responding process can help students with the process of developing the academic literacy they need in order to write essays within specific situational contexts, in this case, the context of the ELAP course. In addition, at a broader level, it can help students to begin the process of being initiated into the culture of the university as a whole.
Keywords: English language -- Study and teaching (Higher) -- Foreign speakers; Rhodes University -- Academic Development Programme; Academic writing -- Study and teaching (Higher) -- South Africa; Educational anthropology -- South Africa; Educational sociology -- South Africa